JENIS-JENIS VEGETASI PENYUSUN HUTAN RAWA GAMBUT BEKAS KEBAKARAN DI DUSUN TALANG SEPUCUK KECAMATAN PEDAMARAN TIMUR KABUPATEN OGAN KOMERING ILIR - Rosanti, Dewi; Mutiara, Dian (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2011)
ABSTRACTResearch of inventaritation of peat swamp vegetation after forest burned was conducted at Talang Sepucuk village in Pedamaran Timur Ogan Komering Ilir, Sumatera Selatan Province on Maret 2006. The objective of this research was Plant was grouth in swamp vegetation after forest burned. This research utilited the direct observation with transect in vegetation growth type during one week. The result of the research gated 2 division, 3 class, 7 order, 9 family, 10 genera and 10 species.Key words : peat swamp, vegetation